Regrowth capacity in relation to defence strategy in Stipa clarazii and Stipa trichotoma, native to semiarid Argentina - Distel, Roberto Alejandro (2007)
Plants can defend themselves against herbivores by either avoiding or tolerating herbivory. Since avoidance mechanisms divert resources to other than growth processes, it could be expected a lower regrowth capacity in species that avoid herbivory than in species that tolerate herbivory, particularly under competition for resources. We tested this hypothesis by quantifying the regrowth of a grazing-avoidant (Stipa trichotoma Nees, synonymous Nasella trichotoma (Nees) Hackel ex Arechav.) and a grazing-tolerant (Stipa clarazii Ball, synonymous Nasella clarazii (Ball) Barkworth) grass species native to semiarid Argentina, when growing either singly or in pairs (one individual of each species) under repeated defoliation in field conditions. Twenty pairs of plants were selected in an area codominated by both species. Plants were protected by a 60 cm-diameter exclosure, in which the rest of the vegetation had been removed. The same procedure was followed with 20 single plants of each species. The same plants were clipped four times in 1996 and 1998 and five times in 1997. The response variable was the cumulative regrowth per plant at the end of each year. The regrowth was analysed for neutral detergent fibre and nitrogen content. Cumulative regrowth of S. clarazii was higher, similar, or lower than the cumulative regrowth of S. trichotoma in 1996, 1997, and 1998, respectively. Regrowth was reduced by interspecific competition, although there was no interaction between species and growing conditions (single or in pairs). Neutral detergent fibre content was consistently higher, whereas nitrogen content was consistently lower, in S. trichotoma than in S. clarazii. Collectively, our results did not support the hypothesis of higher regrowth capacity in the grazing-tolerant species than in the grazing-avoidant species. Further, our findings suggest herbivore tolerance is a previously unappreciated trait of S. trichotoma.